2008
DOI: 10.1098/rstb.2008.0279
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries of the human social brain in the visual, auditory and chemical modalities

Abstract: Structural and functional asymmetries are present in many regions of the human brain responsible for motor control, sensory and cognitive functions and communication. Here, we focus on hemispheric asymmetries underlying the domain of social perception, broadly conceived as the analysis of information about other individuals based on acoustic, visual and chemical signals. By means of these cues the brain establishes the border between 'self ' and 'other', and interprets the surrounding social world in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 258 publications
(283 reference statements)
2
70
0
Order By: Relevance
“…Crucially, our study involves the retrieval of information about genuine social partners associated with long-term relationships rather than responding to arbitrary voice-face pairs learnt in laboratory-based studies. Moreover, although the right hemisphere is involved in the processing of faces, it is widely accepted that the left hemisphere is involved in the categorization of other familiar objects and in matching with sample tasks [14,36,40]. In our study, horses were presented with the sight of the whole body of their owners, and thus may not have been using the face to assign identity.…”
Section: Discussionmentioning
confidence: 95%
“…Crucially, our study involves the retrieval of information about genuine social partners associated with long-term relationships rather than responding to arbitrary voice-face pairs learnt in laboratory-based studies. Moreover, although the right hemisphere is involved in the processing of faces, it is widely accepted that the left hemisphere is involved in the categorization of other familiar objects and in matching with sample tasks [14,36,40]. In our study, horses were presented with the sight of the whole body of their owners, and thus may not have been using the face to assign identity.…”
Section: Discussionmentioning
confidence: 95%
“…However, in the majority of subjects, the direction of trunk movements was inconsistent between the two contacts. Although many aspects of mammalian social behaviour are lateralized at the population level (Brancucci et al, 2009;Rosa Salva et al, 2009), the absence of population-level lateralization in elephants' trunk-to-mouth contacts, is not exceptional. Chimpanzees (Prieur et al, 2016a), gorillas (Prieur et al, 2016b) and orangutans (Rogers and Kaplan, 1996) show no population-level hand preference when touching conspecifics.…”
Section: Animal Behaviourmentioning
confidence: 99%
“…Horses, for instance, preferentially use the right nostril to sniff social odors such as of stallion's feces (McGreevy & Rogers, 2005) and urine of an oestrous mare (Siniscalchi et al, 2015). If the right-sided bias in socio-sexual elephants' behaviour is linked to lateralized olfactory perception, it corresponds to the general pattern of social lateraliza- tion in mammals (Brancucci et al, 2009;Rosa Salva et al, 2009;Rogers et al, 2013). At the same time, the impact of other sensory modalities besides olfaction on the origination of the revealed lateralization cannot be excluded.…”
Section: Animal Behaviourmentioning
confidence: 99%
“…Figure 3.8). Interestingly, the regions selected by RVR were primarily rightlateralized, which follows previous work suggesting hemispheric asymmetries in social perception-specifically, that non-verbal social cues are dominantly processed in the right hemisphere 197 .…”
Section: Motor (Dual Rvrsupporting
confidence: 57%
“…Perhaps more interesting was the strongly right-lateralized effect observed in the visual association network. In general, higher-order visual areas in the right hemisphere are thought to support processing of nonverbal social cues 197 . Previous work has also associated OXTR polymorphisms with differential activity in lateral occipital cortex during emotional face processing 203 , and we have further shown that lateral occipital activity covaries with methylation on CpG site -934 when viewing emotional faces 100 .…”
Section: Oxytocin Social Perception and Predictive Codingmentioning
confidence: 99%